Attainment of Gender Equity and Social Justice for Nigerian Women Through the Implementation of CEDAW'S Right to Choose: an Initiative for the Development of Nigeria - Olatokun, Ganiat Mobolaji (Universitas Negeri Gorontalo, 2022)
The Convention on the Elimination of all forms of Discrimination against Women (CEDAW) is yet to be domesticated and implemented in Nigeria. Hence, its provisions, particularly, Article 16(1) (e) which provided inter alia that, men and women should be given the same right to decide freely and responsibly on the number and spacing of their children, cannot be given effect to. Hence, when it comes to deciding on the number and spacing of children, women in Nigeria are not given any say. This is in contradiction to social justice for women. This equally shows the inequality status of women to men in Nigeria. In order for Nigerian women to enjoy the dividend of gender equality and have access to justice, the attitude of Nigerian men (mostly the uneducated ones, and even some educated ones) of turning their wives into child producing machines must be stopped. Most women in Nigeria are faced with problem of having children yearly in order satisfy their husbands. These women, despite being exposed to health challenges associated with several child births, are usually trapped in a difficult position either to continue production of babies, or to let go their husbands to take another wife. Most women in Nigeria opt for the later. However, it has been viewed by this researcher that if allowed to prosper, the provision of fairness and justice in the distribution of benefits and responsibilities between men and women is well covered by CEDAW's right to choose which is well captured under its Article 16. This is a doctrinal research which utilizes the use of books, journals and internet sources for research. The research concluded that future development based on analysis suggests the full implementation of CEDAW's provision under Article 16.